STARCH PRODUCTION FROM RED GINGER (Zinggiber officinale Rosc.) - Widayat, Widayat; Striadi, H.; Syaiful, Syaiful; Kurnia, Atik; Driastuti, Faradilla (Jurnal Bahan Alam Terbarukan, 2018)
Red Ginger is a natural ingredient including to spice that contain starch 40-60 % weight. Application of red ginger usually it is taken its extract or to taste of traditional food. The purpose of this research is to know the influence of settling time, the red ginger and solvent ratio, and the temperature of the solvent in the production process of red ginger starch. We hope to get the best condition to get the highest starch yield. The process of making red ginger starch begins with peeled, then washed, shredded, filtered and precipitated. Starch ginger dried by the sun's heat. The best result was obtained at 1 hour sedimentation time with red ginger starch yield 13,3%, red ginger and water ratio 3: 5 (g / g) with yield of red ginger 15,69% and temperature of solvent at 25 ᵒC with yield of red ginger starch 11.17%.